BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Fungi of Kerala. V.B. Hosagoudar, T.K. Abraham and P. Puspangadan, Tropical Garden & Research Institute Palode 695562. Thiruvanthapuram, Kerala, India, Aus. 1996 pp 1-151 Price Rs. 120/-. Application of PCR in Mycology. Editors : P.D.Â Bridge, D.K. Arora, CA. Reddy and R.P. Elander,Â CAB international, 1998, 357 pp. Â